Supporting Egypt's Industrial Decarbonization: The Role of DFIs in CBAM Alignment - ElSaid, Malak (AUC Knowledge Fountain, 2025)
The European Union’s (EU) Carbon Border Adjustment Mechanism (CBAM) introduces a new linkage between trade and climate policy by requiring importers to report and pay for embedded emissions. For Egypt, characterized by high trade exposure to the EU through the export of carbon-intensive products, CBAM serves as a regulatory catalyst for industrial transformation, posing significant competitiveness risks. Recent assessments indicate that the Middle East and North Africa (MENA) region faces a significant CBAM burden, approximately three times that of other emerging market and developing economies. Utilizing the Institutional-Capacity Response Model as an analytical tool, this study examines how such external regulatory pressure interacts with domestic institutional alignment and firm-level capabilities to navigate industrial decarbonization. Drawing on a purposive sample of ten semi-structured interviews with industrial leaders and development and policy experts, the research provides a qualitative, exploratory, case-specific assessment of Egypt’s readiness. Findings reveal a structural “capacity trap” defined by: (1) a gap between rising awareness and technical preparedness; (2) weak and non-standardized Monitoring, Reporting, and Verification (MRV) systems; (3) high capital costs; and (4) fragmented policy coordination. The research identifies Development Finance Institutions (DFIs) as critical institutional intermediaries in addressing these barriers. Accordingly, the study recommends establishing an Industrial Decarbonization Accelerator (IDA), an integrated governance and investment platform designed to enable Egypt’s transition from reactive compliance to proactive global competitiveness.